Artikel Implementasi Algoritma Best First Search untuk Pencarian Rute Terpendek pada Aplikasi Cerdas Pendaftaran Santri Baru: Aplikasi Cerdas Pendaftaran Santri Baru - Herfandi Herfandi; Ulfatus Soleha; Agung Susilo Yuda Irawan; Kiki Ahmad Baihaqi; Reza Maulana (SYNTAX Jurnal Informatika, 2022)
Pesantren in Indonesia is a traditional Islamic educational institution that is able to exist until now. A less structured registration process allows errors and delays in the new santri registration process will be easy to occur. Pondok Pesantren Manbaul Ulum in carrying out the education administration process still uses conventional means this causes the service system used has not been efficient and the problem of dormitory limitations, registration regulations must be made in accordance with the distance zone of residence that has been determined. Therefore this study conducted the implementation of the best first search algorithm for the search of the shortest route on the new registration intelligent application. This research resulted in a new santri registration intelligent application by applying the best first search algorithm. The development method uses waterfall. Testing software with black box testing method with test case equivalence partitioning technique gets successful conclusions from various types of testing. With features for santri namely estimation data, home, instructions, contact us, register, login, fill out registration form, see verification, print proof of pass, and see the shortest tute, for admin setting school year, see registration, see registration accepted and rejected and see reports. As for the superadmin, crud admin data and see the report. This application is expected to help pesantren administration and prospective students see the route and support education in the Industrial 4.0 era.